The Effect of Using Phyphox Applications to Improve Learning Outcomes Reviewed from Early Knowledge and Response - Yomianus Bura; Adi Jufriansah; Pujianti Bejahida Donuata (Department of Physics Education, Universitas Mataram, 2022)
This study aims to determine whether or not using the phyphox application affects student learning outcomes in terms of prior knowledge and student responses. This research was conducted in high school, using a quasi-experimental research method (quasi-experimental). The design model of this research was pre-test and post-test using a randomized design by giving an initial test before learning and a final test after learning. In this study, two classes were involved as representatives of the experimental class, given the behavior of learning hypothetical deductive thinking strategies using Phyphox media. In contrast, the control class was used as a comparison of Phyphox tools. The results showed that the experimental class students' learning outcomes were superior to those of the control class. It is shown in the comparison data of the N-Gain value and the results of hypothesis testing. Several covariate parameters also support this research. The percentage change in the practical contribution's value and each parameter's relative contributions shows that the test has improved.